2017
DOI: 10.18203/2394-6040.ijcmph20170743
|View full text |Cite
|
Sign up to set email alerts
|

Lay perspectives on causes and complications of hypertension; and barrier to access health care by known hypertensive patients: a qualitative study from a rural area of South India

Abstract: Background: Global prevalence of hypertension in the year 2000 was estimated to be 26% with approximately 1 billion people affected by it. By 2025 this has been projected to increase to 29% increase to 29%, expecting greater proportion of population will be consists of elderly people. Limited qualitative studies on hypertension are available in India. We intended to conduct a qualitative study on the perception about hypertension causes, complications and barrier to get medications, among known hypertensive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…In the other hand, the timeline and treatment control dimensions had high mean score(8.03±1.512and 8.12±0.725) in comparison to other dimensions in this study which could be interpreted as HTN is lifelong illness but can be controlled by taking medicines therefore patients might be perceived HTN is less severe. The finding of this study is in line with other study which showed similar results (Newtonraj, Arun, Bazroy, & Tovia, 2017). In current study personal control had low mean score than the treatment control which may be due to less confident to follow prescribed behavior treatment and behavior modifications than taking prescribed medications.…”
Section: Discussionsupporting
confidence: 91%
“…In the other hand, the timeline and treatment control dimensions had high mean score(8.03±1.512and 8.12±0.725) in comparison to other dimensions in this study which could be interpreted as HTN is lifelong illness but can be controlled by taking medicines therefore patients might be perceived HTN is less severe. The finding of this study is in line with other study which showed similar results (Newtonraj, Arun, Bazroy, & Tovia, 2017). In current study personal control had low mean score than the treatment control which may be due to less confident to follow prescribed behavior treatment and behavior modifications than taking prescribed medications.…”
Section: Discussionsupporting
confidence: 91%
“…From these records, we retrieved 33 articles, and after going through the full text of these articles, 18 studies were included in the review (figure 1). 26–43…”
Section: Resultsmentioning
confidence: 99%
“…Details of CHIMS discussed elsewhere. 7 Study was conducted among randomly selected 41 eligible participants listed in CHIMS. All women who were at more than 27 weeks of pregnancy residing in the service area were included in the study.…”
Section: Methodsmentioning
confidence: 99%